2004
DOI: 10.1149/1.1770917
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Anisotropic Super Hydrophobic/Hydrophilic Nanoporous Membranes by Plasma Polymerization of C[sub 4]F[sub 8] on Anodic Aluminum Oxide

Abstract: Freestanding anodic aluminum oxide ͑AAO͒ membranes were fabricated using a two-step anodization procedure, voltage reduction method, and inductively coupled plasma polymerization. The fabrication process was monitored with electrochemical and spectroscopic ellipsometry measurements, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and scanning electron microscopy. Static contact angle measurements demonstrated that the two surfaces of the fabricated AAO membranes have dramatically dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Nonetheless, polymer plasma deposition cannot achieve sufficient penetration depth to coat the inner surface of nanoporous materials such as NAA, being limited to surface-based applications [ 106 ]. Modification of NAA platforms with plasma polymer deposition enables the tuning of the hydrophobicity of the surface by polymerizing fluorocarbon monomers using argon or oxygen plasma [ 215 ]. Plasma polymer deposition also changes the chemical and geometrical properties of NAA as platform material in drug delivery systems, where drug release from NAA can be controlled and extended over longer periods of time [ 216 , 217 ].…”
Section: Surface Modification Of Nanoporous Anodic Alumina Photonimentioning
confidence: 99%
“…Nonetheless, polymer plasma deposition cannot achieve sufficient penetration depth to coat the inner surface of nanoporous materials such as NAA, being limited to surface-based applications [ 106 ]. Modification of NAA platforms with plasma polymer deposition enables the tuning of the hydrophobicity of the surface by polymerizing fluorocarbon monomers using argon or oxygen plasma [ 215 ]. Plasma polymer deposition also changes the chemical and geometrical properties of NAA as platform material in drug delivery systems, where drug release from NAA can be controlled and extended over longer periods of time [ 216 , 217 ].…”
Section: Surface Modification Of Nanoporous Anodic Alumina Photonimentioning
confidence: 99%
“…Brenov et al for the first time, reported on the modification of NAA by plasma polymerization [41]. They prepared Janus-type NAA membranes by depositing hydrophobic fluorocarbon polymer from plasma polymerization of C 4 F 8 on one side of the NAA membranes while the other side was left unmodified.…”
Section: Properties Surface Chemistry and Surface Functionalization mentioning
confidence: 99%
“…This technique is particularly efficient and convenient because the ultrathin polymer films of various functionalities can be deposited on any surfaces without the need of surface pre-modification [121]. It is well-established by the first report of plasma treatment on AAO membrane from Brevnov et al [122], who prepared Janus-type membranes with a hydrophilic and hydrophobic side. This approach reported that a super-hydrophobic surface is obtained on AAO membranes using inductively coupled plasma polymerization of fluorocarbon (C 4 F 8 ) monomer, with a water contact angle (WCA) of 150°.…”
Section: Plasma Polymer Depositionmentioning
confidence: 99%